Factors associated with first thrombosis in patients presenting with obstetric antiphospholipid syndrome (APS) in the APS Alliance for Clinical Trials and International Networking Clinical Database and Repository: a retrospective study. (24th October 2018) - de Jesús, GR; Sciascia, S; Andrade, D; Barbhaiya, M; Tektonidou, M; Banzato, A; Pengo, V; Ji, L; Meroni, PL; Ugarte, A; Cohen, H; Branch, DW; et al.
Abstract : Objective: To evaluate the subsequent rate of thrombosis among women with obstetric antiphospholipid syndrome (Ob‐APS) in a multicentre database of antiphospholipid antibody (aPL)‐positive patients, and the clinical utility of the adjusted Global Antiphospholipid Syndrome Score (aGAPSS), a validated tool to assess the likelihood of developing new thrombosis, in this group of patients. Design: Retrospective study. Setting: The Antiphospholipid Syndrome Alliance for Clinical Trials and International Networking Clinical Database and Repository. Population: Women with Ob‐APS. Methods: Comparison of clinical and laboratory characteristics and measurement of aGAPSS in women with Ob‐APS, with or without thrombosis, after initial pregnancy morbidity (PM). Main outcome measures: Risk factors for thrombosis and aGAPSS. Results: Of 550 patients, 126 had Ob‐APS; 74/126 (59%) presented with thrombosis, and 47 (63%) of these women developed thrombosis after initial PM, in a mean time of 7.6 ± 8.2 years (4.9/100 patient years). Younger age at diagnosis of Ob‐APS, additional cardiovascular risk factors, superficial vein thrombosis, heart valve disease, and multiple aPL positivity increased the risk of first thrombosis after PM. Women with thrombosis after PM had a higher aGAPSS compared with women with Ob‐APS alone [median 11.5 (4–16) versus 9 (4–13); P = 0.0089]. Conclusion: Based on a retrospective analysis of our multicentre aPL database, 63% of women with Ob‐APS developed thrombosis after initial obstetric morbidity; additional thrombosis risk factors, selected clinical manifestations, and high‐risk aPL profile increased the risk. Women with subsequent thrombosis after Ob‐APS had a higher aGAPSS at entry to the registry. We believe that aGAPSS is a valid tool to improve risk stratification in aPL‐positive women. Tweetable abstract: More than 60% of women with obstetric antiphospholipid syndrome had thrombosis after initial pregnancy morbidity. Tweetable abstract: More than 60% of women with obstetric antiphospholipid syndrome had thrombosis after initial pregnancy morbidity.